Activation of the Syk tyrosine kinase is insufficient for downstream signal transduction in B lymphocytes - Hsueh, Robert C (BioMed Central, 2002)
BACKGROUND: Immature B lymphocytes and certain B cell lymphomas undergo apoptotic cell death following activation of the B cell antigen receptor (BCR) signal transduction pathway. Several biochemical changes occur in response to BCR engagement, including activation of the Syk tyrosine kinase. Although Syk activation appears to be necessary for some downstream biochemical and cellular responses, the signaling events that precede Syk activation remain ill defined. In addition, the requirements for complete activation of the Syk-dependent signaling step remain to be elucidated. RESULTS: A mutant form of Syk carrying a combination of a K395A substitution in the kinase domain and substitutions of three phenylalanines (3F) for the three C-terminal tyrosines was expressed in a murine B cell lymphoma cell line, BCL(1).3B3 to interfere with normal Syk regulation as a means to examine the Syk activation step in BCR signaling. Introduction of this kinase-inactive mutant led to the constitutive activation of the endogenous wildtype Syk enzyme in the absence of receptor engagement through a 'dominant-positive' effect. Under these conditions, Syk kinase activation occurred in the absence of phosphorylation on Syk tyrosine residues. Although Syk appears to be required for BCR-induced apoptosis in several systems, no increase in spontaneous cell death was observed in these cells. Surprisingly, although the endogenous Syk kinase was enzymatically active, no enhancement in the phosphorylation of cytoplasmic proteins, including phospholipase Cγ2 (PLCγ2), a direct Syk target, was observed. CONCLUSION: These data indicate that activation of Syk kinase enzymatic activity is insufficient for Syk-dependent signal transduction. This observation suggests that other events are required for efficient signaling. We speculate that localization of the active enzyme to a receptor complex specifically assembled for signal transduction may be the missing event.